Etiology of short stature in children attending pediatric endocrinology clinic of a tertiary care hospital in Bangladesh - Karim, Muhammad Rezaul; Shamaly, Kohinoor Jahan; Tithi, Baraka Badrudduja; Akter, Romana; Jahan, Ismat; Begum, Suraiya (International Journal of Contemporary Pediatrics, 2020)
Background: Short stature is a common problem to practicing pediatricians. It results from various etiologies, which are categorized as normal variants and pathological causes. Normal variant short stature consists of Familial Short Stature (FSS) and Constitutional Growth Delay (CGD), while pathological causes are subdivided into endocrine diseases, clinically defined syndromes, chronic diseases, metabolic diseases and others. There are not so much data available in Bangladesh in this respect. So, present study was conducted to know the common causes of short stature. Methods: This cross-sectional study was done in pediatric endocrinology clinic of Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from January 2017 to August 2018. One hundred children with short stature meeting inclusion criteria were recruited after taking an informed consent. The detailed history, physical examination including anthropometric measurements and relevant investigations were done. Data were recorded on a predesigned questionnaire for final analysis. Results: The common causes of short stature identified were familial short stature (FSS) 51% cases, Constitutional Growth Delay (CGD) 14% cases and hypothyroidism 12% cases. Other less common causes of short stature were Growth Hormone Deficiency (GHD) 8% cases, malnutrition 6% cases and genetic syndrome 5% cases. Conclusions: FSS and CGD were the leading cause of short stature in children. Endocrinological causes were the most common cause of short stature after normal variant while nonendocrine causes were the least.